Optimalisasi Peningkatan Dan Penguatan Citra Perpustakaan Melalui Peran Aktif Pustakawan Dalam Aplikasi Teknologi Informasi Komunikasi (TIK) - Dianita Rohmatin Setyani Nugroheni Arisalfika Bakti (Universitas Wijaya Kusuma Surabaya, 2020)
The purpose of this research is trying to describe the role of librarians in optimizing the improvement and strengthening of library images. Research is based on careful analysis based on detailed studies of the focus of content management discussion on the role of librarians in optimizing the improvement and strengthening of library images. The research covers the scope of the analysis of fundamental analysis focusing on the role oflibrarians in the application of information communication technology and library promotion, in order to realize the ideal image of the library, in accordance with the industrial revolution era 4.0. The implementation of analysis requires critical realistic thinking, applying conceptual in the historical period in the past as well as when it is happening, so that it is appropriate to use historical approach research, which requires an investigation characterized by critical critical inquiry into the progress of a thought. Primary information sources are utilized as primary data. The data collection technique utilizes library research, through various literary reading activities subjecting the role of librarians, optimizing library image enhancement and strengthening. The analysis was carried out in a descriptive qualitative manner, based on the analysis of various types of theoretical reading, research and non-research. Research dominates, describes, examines and evaluates various factual facts in order to find solutions to various problems in phenomena. In order to achieve the validity of the analysis, content analysis is needed, which has the benefit of analyzing the meaning of the most important concepts. Observations made are used to support the construction of theory. The results of the study are the ideal image of the library can be achieved through optimizing the role of librarians including; (1). Librarians must have readiness and competency preparation so they can play a maximum role. (2). Librarians must have the ability to apply ICT. (3). Librarians are required to carry out promotions in various ways. (4). Librarians must be able to reflect and evaluate the evaluative power of evaluation and public response when utilizing library information services.